Inheritance Distribution in Islamic Family Law: A Juridical Study of the Principle of Gender Justice - Basri, Basri (PT. Anagata Sembagi Education, 2025)
This article explores the principles of Islamic inheritance law through a normative and conceptual approach, focusing on gender-based distribution and its alignment with the broader ideals of justice in Islamic legal thought. It analyzes classical juristic formulations, particularly the rule that assigns male heirs twice the share of females, in light of maqāṣid al-sharī‘ah and contemporary interpretations of gender justice. The study also compares these principles with customary inheritance practices in Indonesia, which emphasize social roles, flexibility, and deliberation-based distribution. The findings reveal an ongoing tension between the rigidity of classical fiqh and the evolving demands of justice in pluralistic and modern contexts. By synthesizing classical doctrines with maqāṣid-oriented reasoning and contextual ijtihād, the study demonstrates the potential for a more responsive and ethically grounded inheritance framework. This research contributes to the broader discourse on Islamic legal reform by highlighting how contextual reinterpretation of inheritance norms can reflect not only legal continuity but also the living spirit of sharī‘ah justice in addressing gendered realities.